2017
DOI: 10.1021/acs.joc.7b00464
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-Catalyzed C–N Bond Formation: Synthesis of 3-Aminoquinoxalinones under Ambient Conditions

Abstract: A metal-free cross-dehydrogenative coupling between quinoxalinones (sp C-H) and amines (N-H) in the presence of catalytic iodine is reported. The reaction yields 3-aminoquinoxalinones in moderate to high yields under ambient conditions in dioxane as solvent and aqueous tert-butyl hydroperoxide (TBHP) as the terminal oxidant. The reaction is highly versatile and exhibits good functional group tolerance with a range of primary and secondary amines. It provides a practical access to pharmaceutically active 3-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…In this regard, Gulevskaya et al reported the first direct oxidative CÀH amination of quinoxalin-2(1H)-ones without the prefunctionalized steps. More recently, Jain et al successfully developed an iodine-catalyzed synthesis of 3-aminoquinoxalinones (Scheme 1), [7] wherein, 2 equiv. Recently, Cui [5] and Phan [6] independently reported the copper-catalyzed CÀH amination of quinoxalin-2(1H)-ones for the synthesis of 3-aminoquinoxalinones (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Gulevskaya et al reported the first direct oxidative CÀH amination of quinoxalin-2(1H)-ones without the prefunctionalized steps. More recently, Jain et al successfully developed an iodine-catalyzed synthesis of 3-aminoquinoxalinones (Scheme 1), [7] wherein, 2 equiv. Recently, Cui [5] and Phan [6] independently reported the copper-catalyzed CÀH amination of quinoxalin-2(1H)-ones for the synthesis of 3-aminoquinoxalinones (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant progress, only limited examples for the synthesis of 3-aminoquinoxalinones via direct CÀH amination under metal-free conditions have been reported. More recently, Jain et al successfully developed an iodine-catalyzed synthesis of 3-aminoquinoxalinones (Scheme 1), [7] wherein, 2 equiv. of TBHP as the oxidant was necessary for this transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Pd (OAc) 2 was used as a catalyst for this reaction, no product 3a was obtained (entry 2). Next, given that the C‐N coupling reactions in the presence of I 2 had been reported, I 2 was used as catalyst, but the reaction gave no desired product 3a (entry 3). Therefore, various copper salts, such as CuBr, CuCl, CuI, Cu (OAc) 2 , and CuCl 2 , were used in the C‐N coupling reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular iodine has been applied as efficient, ecofriendly and readily available catalyst for many transformations in synthetic organic chemistry. [24] Due to the oxidative changes from the molecular iodine, this compound was extensively applied as catalyst for CÀ C, [25] CÀ O, [26] CÀ N, [27] CÀ S, [28] and N-S [29] bond formations. In addition, recently it was applied as catalyst for the preparation of 3,4-disubstituted-5-imino-1,2,4-thiadiazoles from N-arylbenzamidines and isothiocyanate, [30] aminosubstituted 1,2,4-thiadiazoles from substituted N-carbamothioylamidines or N-carbamothioylguanidines, [31] and 1,2,4-thiadiazoles from nitriles and thioamides.…”
Section: Introductionmentioning
confidence: 99%